Chapter Ludovica Torelli e lo Specchio interiore di fra' Battista da Crema - Murano, Giovanna (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The Specchio interiore (Interior Mirror) is a work by the dominican Fra' Battista da Crema partly dedicated to the theme of mystical union. Written close to the foundation, in 1522, of the Hospital of the Incurables in Venice, it remained unpublished for almost two decades and it was first published in 1540 thanks to Ludovica Torelli, countess of Guastalla (1499-1569), alias Paola Maria. Widow, for the second time at age twenty-eight, Ludovica Torelli enjoyed an unusually powerful position for a women. Forced to sell her small state to Ferrante Gonzaga, she spent the second part of her life founding religious institutions and hospitals in Milan and other cities in northern Italy.